2016
DOI: 10.15314/tjse.79586
|View full text |Cite
|
Sign up to set email alerts
|

Examining the physical education teacher concept related metaphor perceptions of secondary school students

Abstract: The purpose of the present research was to examine the perceptions of 6 th Grade students (age range: 10-13 years old) regarding their concept of the physical education teacher expressed through metaphors and to analyze these metaphors for comparison between the genders. A total of 356 students (girls=184; boys=172) participated in the study during the 2014-2015 academic year. They were from three different state schools in the province of Konya, Turkey. According to the results, the students produced 67 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The results of our research also show parallelism with the relevant studies in the literature and show that students generally form positive metaphors for physical education teachers (Soysal & Afacan, 2012;Kalyoncu, 2012;Gedikli, 2014;Çulha-Özbaş & Aktekin 2013;Şengül et al, 2014;Sayar, 2014;Gorucu et al, 2016;Ulas, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of our research also show parallelism with the relevant studies in the literature and show that students generally form positive metaphors for physical education teachers (Soysal & Afacan, 2012;Kalyoncu, 2012;Gedikli, 2014;Çulha-Özbaş & Aktekin 2013;Şengül et al, 2014;Sayar, 2014;Gorucu et al, 2016;Ulas, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…When the relevant studies in the literature were examined, it was found that the researchers focused on the physical education lesson (Koksal & Gorucu, 2015;Sofi & Yoncalik, 2015;Karagün, 2021;Güllü, 2021;Stylianou et al, 2013;Carlson, 2001) and the number of studies on teachers was quite low (Sözen & Korur, 2019;Gorucu et al, 2016;Ulas, 2021). In addition, the fact that the students who have just started secondary school are taking the physical education lesson from the physical education teacher for the first time reveals the situation of the students to face a new situation.…”
Section: Introductionmentioning
confidence: 99%
“…Tsakiris et al (2009) reported that vitamin E and vitamin A supplementation in a group of 10 basketball players caused lower increases in blood lactate levels after exercise [32]. Goruku (2017) investigated the effects of vitamin E and A supplementation on some haematological parameters in a group of taekwondo elite players on a period of 6 weeks, suggesting positive effects of the mentioned vitamins on hematocrit (HCT), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), mean platelet volume (MPV), procalcitonin (PCT) and lactate levels [33].…”
Section: Resultsmentioning
confidence: 99%
“…In the study of İlhan and Karaşahinoğlu [28], it was seen that students portrayed their physical [24], students expressed their opinions about physical education teacher being athletic/sportsman, understanding/friend-like, and fun/cheerful. Research by Gorucu et al [27] similarly identified the students' metaphors about physical education teacher as friend, father, comedian, and trainer.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, separate studies have been conducted on the attitudes of secondary school students toward PEL [15]- [22] their attitudes and perceptions towards physical education teacher [23]- [26] and their metaphorical perceptions on these issues [27]- [30]. There has not been a study in the literature that has been done both quantitatively and qualitatively by bringing all of them together.…”
Section: Introductionmentioning
confidence: 99%